Triple Surgical Fixation Technique for an Isolated Greater Trochanter Fracture in an Amateur Weightlifter. (9th May 2022) - Sanderson, Brent; Washburn, Frederic; Allison, Daniel
Abstract : Isolated greater trochanter fractures have been infrequently described in the literature and are typically managed conservatively. Functional strength after injury to the abductor complex can be markedly affected resulting in a Trendelenburg gait and overall abductor weakness. We present a case of a 35-year-old athlete who underwent surgical fixation because of notable fracture displacement and function debility. This case vignette demonstrates the importance of using all available interdisciplinary orthopaedic surgery literature to provide a patient-specific surgical construct. Our patient benefitted from arthroscopic, arthroplasty, and trauma evidence-based medicine to successfully treat his displaced greater trochanteric hip fracture. Successful surgical fixation was enhanced by combining three different methods of fixation: osteosynthesis with partially threaded screws and washers (DePuy Synthes), suture anchor (Arthrex) direct fracture approximation and tendon reinforcement, and a knotless double-row suture bridge (Arthrex) tension band construct. The patient was able to return weightlifting at 4 months postoperatively with no evidence of weakness or trendelenburg gait.